Weeb Student Self-Concept Due to Action Anime: Case Study in Syekh-Yusuf Islamic University, Tangerang - Khumaeroh, Eroh; Sartika, Helena Mufti; Fauzi, Ilham Herda; Ibrahim, Wisnu Maulana Malik (Kalijaga Journal of Communication, 2023)
Anime is a Japanese cartoon film that is very popular among adults, teenagers, and children. As a result, many people change their self-concept to their life behavior to be the same as anime characters. This study aims to elaborate on the formation of the self-concept of a weeb or anime lover in everyday life. The research method used is a descriptive qualitative method with a case study approach. Data collection was carried out by interviews and observations on anime lovers at Syekh-Yusuf Islamic University's 7th-semester Communication Science study program. This research focuses on how individuals or weebs find their identity and concepts in themselves after watching anime films. This research applies Sven Windahl’s theory of uses and effect. The results showed that this self-experience encouraged subjects to learn Japanese and also gave freedom to imagine and interacting with their favorite anime characters.